Effect of 12 Weeks of Endurance Training on Plasma Levels of Apelin-13, Insulin, and Glucose in Obese Male Rats - zahra Rostami Hashjin; Abbasali Gaeini; Rouhallah Haghshenas (Shahid Beheshti University of Medical Sciences, 2021)
Background and Aims: Apelin is a newly discovered adipokine whose level is high in obese people with insulin resistance. It is not clear how endurance training affects apelin plasma levels. The present study aims to investigate the plasma levels of apelin-13, insulin, and glucose in obese male rats following 12 weeks of endurance training. Methods: Samples were 14 obese male Wistar rats who received high-fat food for eight weeks to become fat based on the Lee obesity Index. The rats were then randomly divided into control (n=7) and training (n=7) groups. The training group ran on a treadmill with zero slope for 12 weeks, 5 days per week (60-min sessions at a speed of 15-30 meters per minute). The ELISA method was used for measuring the levels of apelin-13 and insulin, while photometric glucometer was used measuring the glucose level. Results: The results of independent t-test showed that there was a significant difference between plasma levels of glucose (P=0.0001), insulin (P=0.0001) and apelin (P=0.041) in obese male rats of control group and endurance test. The results of independent t-test showed a significant difference in plasma levels of glucose, insulin, and apelin-13 between the two groups (p < 0.05). The glucose and insulin levels in the training group were lower than in the control group , while the apelin-13 level was higher in the training group. Pearson correlation test results showed no significant relationship between levels of apelin-13 and insulin (P=0.07) as between apelin-13 and glucose (P=0.055) after 12 weeks of endurance training. Conclusion: It seems that 12 weeks of endurance training can reduce the plasma levels of insulin and glucose and increase the plasma level of apelin-13 in obese male rats.